Phenotypic and genetic characterization of soybean (Glycine max) genotypes for yield and drought stress tolerance - Mehmood, Khalid; Khan, Dilawar; Saeed, Muhammad; Khajjak, Malik Asad Khan; Ata ur Rehman; Khetran, Abdul Sattar; Rasool, Ghulam; Ullah, Atta (Journal of Pure and Applied Agriculture, 2023)
Soybean is the world’s major oilseed crop which provides a significant amount of high-quality protein and edible oil. The Present research work was designed to assess the phenotypic variability, genetic characterization, and drought tolerance in soybean genotypes. A total of eight soybean genotypes were studied for field experiments during the year 2019 using Randomized Complete Block design (RCBD)at Balochistan Agriculture College, Quetta. Mean squares from Analysis of Variance (ANOVA) showed considerable phenotypic variation for most of the studied traits including plant height, maturity duration, pod length, number of seeds per pod, 100-seed weight, and seed yield plant-1. The molecular genetic diversity among studied genotypes was confirmed through seven Simple Sequence Repeat (SSR) markers. Molecular data was scored qualitatively for the presence and absence of polymorphism using gel banding patterns. Out of seven SSRs, only four markers amplified and showed polymorphism. Molecular diversity displayed four major clusters at a 0.62 level of coefficient. Among the studied genotypes two lines namely, CH-NEsp-17 and Ertou # 2 showed high genetic diversity. Furthermore, the drought resistance of soybean genotypes was also determined through diaminobenzidine (DAB) staining process by using fresh leaves of each genotype with two treatments. Three genotypes, namely Ajmeri-2, CH-NEsp-17, Jhunghwang showed drought tolerance in both i.e., control as well as drought stress. However, genotype Ertou # 2 was found to be most susceptible.The results further demonstrated that the genotypes which showed high seed yieldwere also founddrought tolerance.Thus, this study mayfaciliate futrure breeding programs in developing new soybean cultivars for high yield potential anddrought resistance of soybean.